Gastric emptying of fluids during variable-intensity running in the heat - Gant, N.; Leiper, J. B.; Williams, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
This study examined gastric emptying, core temperature, and sprint performance during prolonged intermittent shuttle running in 30 °C when ingesting a carbohydrate-electrolyte solution (CES) or flavored water (FW). Nine male soccer players performed 60 min of shuttle running, ingesting fluid before exercise and every 15 min during exercise. Gastric emptying was measured using a double-sampling aspiration technique, and intestinal temperature was monitored via ingested capsules. There were no differences between trials in the total fluid volume emptied from the stomach during each exercise period (P = 0.054). The volume emptied every 15 min was 244 ± 67 mL in the CES trial and 273 ± 66 mL in the FW trial. Intestinal temperature was higher during exercise in the CES trial (P = 0.004), and cumulative sprint time was shorter (P = 0.037). Sprint performance was enhanced by the ingestion of a CES, which resulted in elevated core temperatures, and the rate of gastric emptying remained similar between solutions.